INFLUENCE OF HILLS AND VALLEYS ON FREE SURFACE SLIP AMPLIFICATION IN DYNAMIC RUPTURE ON A DIPPING FAULT - R. Parla; S. N. Somala (Геодинамика и тектонофизика)
Dynamic rupture scenarios on various fault geometries are studied extensively in the literature for domains with the planar top surface. However, landscapes on the earth, particularly in tectonic regimes, can undulate upwards or downwards depending on faulting conditions. In this paper, we studied a dipping fault model with a dip fault angle of 60 degrees, inspired by the 2D version of dynamic rupture benchmark TPV10 from the Southern California Earthquake Center (SCEC). A topographic feature adjacent to the fault is introduced in the form of a hill or a valley. The shape of the undulation was varied from semi-circular form to Gaussian profile. This paper examines the impact of topographic features (valleys or hills) on slip amplitude on a fault. The distance at which the features exist also affects the amount of slip on fault, ruptured in that region. The results for a couple of different radii of semi-circular formation and equivalent standard deviation of Gaussian undulation are also summarized in this paper. The study depicts that the topography in the vicinity of the fault can affect the magnitude of slip propagation on fault surface.